Volume 2A: Turbomachinery 2015
DOI: 10.1115/gt2015-42617
|View full text |Cite
|
Sign up to set email alerts
|

Steady and Unsteady CFD Calculation of the Laminar-to-Turbulent Transition in a Turning Mid Turbine Frame With Embedded Design

Abstract: In order to meet the weight requirements of future jet engines S-shaped intermediate turbine ducts can be supplied with turning load carrying struts in order to save the first vane row of the subsequent low pressure rotor. In such a duct large flow structures emanating from the outlet of the transonic high pressure stage are transported towards the low pressure rotor and are superimposed by secondary effects generated by the turning struts within the duct. To reduce the fluctuations behind the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Whereas the highest loss occurs in the strut wake in the baseline design, the losses are more evenly distributed in the embedded design. In a succeeding study of the unsteady flow, Spataro et al [12] and Bader et al [14] proved experimentally and numerically a positive effect. Both publications showed a damping of the unsteady fluctuation by the splitters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the highest loss occurs in the strut wake in the baseline design, the losses are more evenly distributed in the embedded design. In a succeeding study of the unsteady flow, Spataro et al [12] and Bader et al [14] proved experimentally and numerically a positive effect. Both publications showed a damping of the unsteady fluctuation by the splitters.…”
Section: Discussionmentioning
confidence: 99%
“…Spataro et al already showed in steady [11] and unsteady [12] measurements the reduction of the nonuniformity of pressure fluctuations (reduced strut wakes and secondary vortices) of the embedded design. In addition to the measurements, steady [13] and unsteady [14] computational fluid dynamics (CFD) simulations have been performed at the Institute for Thermal Turbomachinery and Machine Dynamics to analyze the flow structures within the TMTF with the embedded design.…”
mentioning
confidence: 99%
“…The state of this boundary layer, whether it is laminar or turbulent, is on one hand influenced by free stream parameters, like the velocity, acceleration or turbulence level of the free stream and on the other hand influences the free stream itself as well as wall parameters, like skin friction or heat transfer (see e.g. Bader and Sanz [2015]).…”
Section: Introductionmentioning
confidence: 99%